KEPADATAN JAMUR MIKORIZA VESIKULAR ARBUSKULAR (MVA) DI KAWASAN HUTAN MANGROVE DESA PENITI KABUPATEN MEMPAWAH KALIMANTAN BARAT - Hartini, Hartini; Linda, Riza; Rahmawati, Rahmawati (Universitas Tanjungpura, 2019)
Mycorrhizal fungi are fungi that are associated with higher levels of plants and are very important in plant growth. Mycorrhizal fungi can be found most of the land, one of which is in the mangrove forest. This study was conducted to determine the type of fungus and the percentage of infections in plant roots and fungal density of VAM found in the Mangrove Forest area at Mempawah Regency, West Kalimantan. This research was conducted at the Microbiology Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences. Analysis of soil chemical content was carried out in the Laboratory of Chemical and Soil Fertility, Faculty of Agriculture, Tanjungpura University. Isolation of spores was carried out by wet filter method and continued with centrifugation. The results indicated that the spores found consisted of 3 genera were Glomus, Gigaspora and Paraglomus. The percentage of root infections by mycorrhizal fungi was classified as low at 10.65%, and density of VAM fungus spores in Parit Tanjung as many 13 spores, Kasim as many 10 spores, Sungai Burung as many 59 spores and Tanjung as many 33 spores.